Portal vein thrombosis with protein C-S deficiency in a non-cirrhotic patient - Deshpande, Sheetal; Patil, Smita; Pendse, Manish; Kashyap, Prashant; Dave, Dhaval (International Journal of Research in Medical Sciences, 2016)
There are several conditions that can lead to portal vein thrombosis (PVT), including including infection, malignancies, and coagulation disorders. Anew condition of interest is protein C and S deficiencies, associated with hypercoagulation and recurrent venous thromboembolism. We report the case of a non-cirrhotic 24-year-old male diagnosed with acute superior mesenteric vein thrombosis and PVT and combined deficiencies in proteins C and S.